The dichotomy of teaching in the face of emergency virtualization in education in the context of the Covid-19 pandemic (Research, Society and Development, 2022)
With the advance of Covid-19 in the world it was generated a series of impacts on the activities performed by the population, through the limitations imposed by isolation and social distance. In this context, this study aimed to analyze from the teachers' inferences the positive and negative points of remote work in the emergency virtualization process. The qualitative methodology has been used with critical interpretations in this case study format. We conclude that remote work points out to several elements to rethink about the paradigms that emerges in education and that leads us to re-signify the teaching and learning process by means of the limitations imposed by the social isolation caused by Covid-19.